2002
DOI: 10.1172/jci0215640
|View full text |Cite
|
Sign up to set email alerts
|

Immune complex–mediated antigen presentation induces tumor immunity

Abstract: Antigen uptake receptors on dendritic cells (DCs) provide efficient entry for the initiation of antigen-specific adaptive immunity. Here we show that targeting of antigen to Fc receptors on DCs accomplishes combined activation of Th1 CD4 and CD8 effector responses in vivo, namely delayed-type hypersensitivity and tumor immunity. Tumor immunity specific for ovalbumin-expressing tumors was provided by immunization with wild-type but not FcgammaRgamma(-/-) DCs loaded with ovalbumin-containing immune complexes. Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(116 citation statements)
references
References 46 publications
5
111
0
Order By: Relevance
“…Thus FcγR--targeting strategies which utilize the IgG-Fc domain to target Ag to FcγR can bind FcγRIIB on B cells and DC and potentially dampen Ag-specific Ab responses as well as DC-mediated T-cell activation. Despite this, numerous studies, including our own, demonstrate the efficacy of targeting Ag to FcγR (Adamova et al 2005;Amigorena and Bonnerot 1999;Celis et al 1984;Gosselin et al 1992;Guyre et al 1997;Heijnen et al 1996;Heyman 2000;Jelley-Gibbs et al 1999;Moore et al 2003;Rafiq et al 2002). In fact, recent studies by others have demonstrated that enhanced immune responses can be generated with mAb-Ag complexes despite mAb-Ag interaction with FcγRIIB.…”
Section: Inhibitory Receptorsmentioning
confidence: 89%
“…Thus FcγR--targeting strategies which utilize the IgG-Fc domain to target Ag to FcγR can bind FcγRIIB on B cells and DC and potentially dampen Ag-specific Ab responses as well as DC-mediated T-cell activation. Despite this, numerous studies, including our own, demonstrate the efficacy of targeting Ag to FcγR (Adamova et al 2005;Amigorena and Bonnerot 1999;Celis et al 1984;Gosselin et al 1992;Guyre et al 1997;Heijnen et al 1996;Heyman 2000;Jelley-Gibbs et al 1999;Moore et al 2003;Rafiq et al 2002). In fact, recent studies by others have demonstrated that enhanced immune responses can be generated with mAb-Ag complexes despite mAb-Ag interaction with FcγRIIB.…”
Section: Inhibitory Receptorsmentioning
confidence: 89%
“…In a murine model, ovalbumin and anti-ovalbumin immune complexes given to DCs were able to generate ovalbuminspecifi c T-cell responses. These responses depended on the presence of FcγR, the antigen-processing component transporter associated with antigen processing (TAP), β 2 -microglobulin, and major histocompatibility complex II on the DCs, indicating the importance of the FcγR-mediated enhancement of the TA cross-presentation pathway [40]. Similarly, treatment of apoptotic myeloma cells with anti-syndecan-1 mAb before incubation with DCs caused tumor cell phagocytosis and subsequent melanoma-associated antigen-specifi c T cell activation [41].…”
Section: Induction Of T-cell Activation By Monoclonal Antibody Therapymentioning
confidence: 99%
“…In tissues, DCs and DC precursors capture antigens from a wide range of sources including bacteria, viruses, dead or dying cells and extracellular proteins, peptides and immune complexes. DCs have a host of different antigen uptake receptors for this purpose, including scavenger receptors [19], Fc receptors [20,21] and C-type lectins [22,23]. Some of these receptors induce simultaneous uptake and stimulatory signals, whereas others are inhibitory receptors that induce suppressive signals upon antigen uptake.…”
Section: Antigen Uptake and Maturationmentioning
confidence: 99%